The Discontinuous Carbon Fiber Composite: A Review of the Damage Characteristics - Jefri S. Bale (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2015)
Abstract Discontinuous carbon fiber composite (DCFC) is one of new low-cost material product form that had applied for commercial component such as window frames of the Boeing 787 Dreamliner. Study on DCFC was very challenging since it did not have the same nature behavior like conventional composite nor isotropic materials. In this work several studies on damage characteristics of DCFC material were presented. The damage characteristics of DCFC were investigated while undergoing static and fatigue loading. In particular, the damage mechanisms of DCFC were also observed through several nondestructive testing (NDT) methods. The review had shown that the study of DCFC specimen gives an interesting challenges for the future work to understand its damage characteristics and the reliability of the NDT method to study the damage of DCFC material.